PERBEDAAN KUALITAS TIDUR MAHASISWA YANG MEROKOK DENGAN YANG TIDAK MEROKOK DI FAKULTAS HUKUM UNIVERSITAS RIAU - Monita Diameris Harahap; Darwin Karim; Febriana Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Smoking behavior is a social phenomenon that is often encountered in everyday life that begins at a young age. Smoking habits are followed by activities staying up or awake at night. The purpose of this study is to determine thedifference of quality of sleep students who smoke and non-smokers. This research uses comparative research designwith cross sectional approach. The sample was 82 respondents, consisting of 41 male students of smokers and 41 nonsmokermale students. Samples were taken using purposive sampling technique. The measuring instruments used arethe PSQI (Pittsburgh Sleep Quality Index) questionnaire and smoking behavior. The result of univariate analysisshowed that the majority of respondents were in the age range of 20-24 years as many as 63 people (76.8%), theaverage respondents had poor sleep quality, 49 respondents (59,8%), as bad as 37 people (90,2%) while non-smokingstudent with poor sleep quality amount to 12 people (29,3%). The result of bivariate analysis showed that there was adifference between the sleep quality of the students who smoked and those who did not smoke (p value <α = 0,05)(0.000 ˂ 0,05). Based on the results of this study researchers suggest to the public, especially students not to smoke andto know the impact of smoking that can affect the quality of sleep or health. Keywords: Sleep quality, smokers, non-smokers, students